O comércio varejista em Uberlândia (MG) e sua atuação como agente modificador do espaço urbano: as estratégias da rede Bretas de supermercados - Lopes, Michelly de Lourdes (2012)
The trade, seen as one of the main urban functions, even being defended the thesis that the historical evolution of the city has been directly influenced by goods trade, is urban space modifier, especially in a society ruled by the capitalist mode of production. Initially concentrated in the central areas of the cities, the trade activities have been suffering a decentralization process, especially regarding large retailers developments, leaving the central areas in search of decentralized areas, but they are supplied by proper infrastructure and facilities that make the place attractive. This way, the commercial developments enter the urban space in order to change its dynamics and at the same time take advantage of amenities previously installed, given the privileged locations that commercial structures aim, creating new centers in space and changing the flow direction. Seen this, Uberlândia is taken as study area for its particular socioeconomic dynamics and for its role in the national and state scenario, having the economy focused on the tertiary sector (trade and services), and is characterized by great complexity and dynamism in the organization of its urban space. In this sense, this research aims to understand the strategies of a supermarket chain, the chain Bretas in the city of Uberlândia, MG, where there are nine open stores. Originated in the State of Minas Gerais, the chain uses strategic plan to guide their actions, which allows, among others, a privileged location in the urban space, guided by the market rules. In order to reach the goal, the work is structured in three chapters, prepared using the methodological procedures established, the main ones are: bibliographic research and preparation of theoretical reference, historical reinterpretation of the city of Uberlândia and of the business trajectory of Bretas Group, in loco visit at researched stores and specialized retailers magazines and newspapers. In the end of the work, there is a clear concern of the company to act on the basis of strategic planning, which allows greater safety in the investment, promoting the expansion characteristic of the group, and its locational strategy that ensures the proximity with the customers. In addition, through their strategies, it was realized that the chain is attentive to the target public, structuring itself and diversifying its products and services according to the type of customer intended for each store, based on its the coverage area. Having used the marketing, the chain promotes the idea of low prices linked to the safety and convenience as a way to attract customer.intra-urban; retailer trade; Chain Bretas